Alion, Sencor, and Sharpen for Preemergence Kochia Control in an Abandoned Alfalfa Field - R. Currie; P. Geier (Kansas Agricultural Experiment Station Research Reports, 2016)
Alion (indaziflam) combined with Sencor (metribuzin) were the most effective herbicides for kochia control. Sharpen (saflufenacil) alone or with Prowl H2O (pendimethalin), Sencor, or Alion was less effective at controlling kochia compared to Alion plus Sencor. By 91 days after treatment (DAT), Alion at rates above 3 oz/a plus Sencor were more effective than lower rates for kochia control. However, all Alion plus Sencor treatments were better than Sharpen-containing tank mixes 91 DAT.
Keywords: weed control; preemergence applications; kochia; abandoned alfalfa field; alfalfa; Alion; Indazaflam; Sencor; metribuzin; Sharpen; Saflufenicil